Towards a measure of financial fragility - Aspachs, O; Goodhart, C; Zicchino, L (University of Oxford, 2006)
This paper proposes a measure of financial fragility that is based on economic welfare in a general equilibrium model calibrated against UK data. The model comprises a household sector, three active heterogeneous banks, a central bank/regulator, incomplete markets, and endogenous default. We address the impact of monetary and regulatory policy, credit and capital shocks in the real and financial sectors and how the response of the economy to shocks relates to our measure of financial fragility. Finally we use panel VAR techniques to investigate the relationships between the factors that characterise financial fragility in our model, i.e. banks' probabilities of default and banks' profits - to a proxy of welfare.